VILIP3 attenuates neuronal apoptosis and oxidative stress via Nrf2 activation in the pathogenesis of Alzheimer’s disease - Shasha Huangfu; Xiaoyu Sang; Shiyue Zhou; Haixia Liu; Dongqing Cui; Yansheng Du; Xinyue Xing; Wenyan Liu; Jianzhong Bi; Zhaohong Xie (Molecular Medicine)
Abstract Background Alzheimer’s disease (AD) is a common neurodegenerative condition characterized by amyloid-β protein (Aβ) deposition, which is central to its pathological changes. Oxidative stress also plays an important role in its pathogenesis. Visinin-like protein 3 (VILIP3), a neuronal calcium sensor protein, is abnormally expressed in the brains of patients with AD; however, the exact mechanism remains unclear. This study investigated the role of abnormal VILIP3 expression in AD pathogenesis and its underlying mechanisms. Methods We used 5×FAD mice as an in vivo model of AD and Aβ1−42-treated SH-SY5Y cells to construct an in vitro model. Changes in VILIP3 expression were assessed in both models. VILIP3 was overexpressed in the hippocampus of 5×FAD mice and SH-SY5Y cells using adeno-associated virus (AAV) or plasmid transfection. Cognitive function, Aβ deposition, neuronal damage, synaptic plasticity, apoptosis, oxidative stress, and other relevant indices were evaluated. Results VILIP3 was expressed at lower levels in AD model mice and cells than in controls. Overexpression of VILIP3 ameliorated cognitive deficits, reduced Aβ deposition and neuronal loss in 5×FAD mice, and attenuated oxidative stress levels and apoptosis in 5×FAD mice and Aβ1−42-treated SH-SY5Y cells. Furthermore, VILIP3 activated nuclear factor E2-related factor 2 (Nrf2) and increased the expression of downstream antioxidant genes. The amelioration of apoptosis and oxidative stress by VILIP3 was blocked by Nrf2-specific inhibitors. Conclusions VILIP3 mitigates oxidative stress and apoptosis by activating the Nrf2 signaling pathway, thereby alleviating neuropathological damage and cognitive dysfunction in AD.